Crossing paths with alumni - Chan, Margaret Kit Yok (UiTM Sarawak, 2016)
The main objective of almost all conferences, seminars and forums is to bring together academicians, researchers and practitioners working in the respective fields of all over the world in order to exchange information and bring new contribution. Thus attending a conference is a professionally rewarding experience which gives not only the opportunity to socialize with colleagues from other institutions but also a trip to an exotic locale possible. During the last six months, I was able to catch up with some Diploma in Plantation and Industrial Management graduates and realized how much "grown-up" they have become as they are successfully established in their respective careers.